Motyw niezgody rodzinnej w rosyjskiej beletrystyce o życiu duchowieństwa lat 1860–1870 - Łukaszewicz, Marta (Studia Rossica Posnaniensia, 2011)
In the present paper the analysis of a motif characteristic of the Church-oriented novels, novelettes, stories and sketches – the motif of family discord – is offered. The examination of several literary works of the 1860s and 1870s has shown that it is the depiction of the negative aspects of clergymen's family life that dominates, the reasons for which being different moral principles, hierarchy of values and major life objectives. Usually it is a priest's wife that is presented as a negative character, although the opposite may be also observed. In the paper both the influence of the literary motif of family discord, popular in the realistic literature, is examined and certain facts of everyday life of the Orthodox clergy are presented in order to show the combination of these factors in the Church-oriented literary works.